Expanding gray zones in ERCC2 mutations; a patient with XP phenotype and acute post-infectious leukodystrophy - Akyüz, Enes; Şahin, Türkan Uygur; Ozbarutcu, Ebru Baran; Aralaşmak, Ayşe; Yeşil, Gözde (Eastern Journal of Medical Sciences, 2019)
Mutations in ERCC2, a Nucleotide Excision Repair (NER) gene leads to Xeroderma pigmentosum (XP), Trichothiodystrophy (TTD) and Cockayne Syndrome (CS) phenotypes with various severities. While patients undergo XP disease are primarily suffering from skin hypersensitivity but rarely having central nervous system problems, TTD and CS patients are mostly having neurological disorders. In addition to that severe changes in hair and nail texture are especially unique to TTD. Hereby we report a previously healthy patient developed a rapid neurological decline and severe leukodystrophy due to an acute infection in which kept up with mild UV sensitivity and mild developmental delay. Pathophysiology of infection related neurodegeneration and DNA repair genes are also discussed.